Diagnostic value of ultrasonographic combining biochemical markers for Down syndrome screening in first trimester: a meta‐analysis. (28th June 2015) - Liu, Yang; Ye, Xingguang; Zhang, Na.; Zhang, Baohuan; Guo, Congcong; Huang, Weihuang; Jing, Lipeng; Wang, Man; Yang, Guang; Wei, Xiangcai; Jing, Chunxia
<x xml:space="preserve">Abstract</x> What's already known about this topic? Different combinations of MA and NT and NB and free β‐hCG and PAPP‐A have been used in the first trimester to screen for Down syndrome; however, the sensitivity and specificity of these screening tests varied among studies. What does this study add? This is the first meta‐analysis that analyzes the diagnostic value of four different combining tests by MA and NT and NB and PAPP‐A and free β‐hCG for Down syndrome. It shows that the combination of NT and PAPP and free β‐hCG is a cost‐effective diagnostic tool for Down syndrome. © 2015 John Wiley & Sons, Ltd.